RELATIVES’ GATECRASHING IN THEIR OFFSPRING’S PRIVATE LIFE: A STUDY OF TUNJI OGUNDIMU’S THE INSIDERS AND AMMA DARKO’S BEYOND THE HORIZON - GBAGUIDI, CELESTIN (My University, 2014)
This paper lays bare the injustice and relatives’ interference in children’s love affairs leading young lovers to a conflicting relationship, which causes their marriage bonds to break up through Amma Darko’s Beyond the Horizon and Tunji Ogundimu’s The Insiders. It aims to bring to light the suffering children often endure when their parents or the extended family impose on them the companion that they have to marry and make people aware that marriage is after all an individual concern.
Keywords: Gatecrashing – marriage – selfishness – private life – poverty – literary works